Product Management Fundamentals - LeMay, Matt (O'Reilly Media, Inc., 2017)
Positioned at the intersection of business, design, and technology, product management has emerged as one of the most critical business roles of the 21st century. But what does a product manager actually do? What impact can a great product manager have on an organization? And how do you know what makes a product manager great in the first place? This video covers the fundamentals of product management-what it is, who does it, and how it varies from organization to organization. It offers a new model for understanding the communication, organization, research and execution (CORE) connective skills of product management and provides actionable guidelines for succeeding in product management in any organization of any size. Understand the key responsibilities and CORE connective skills of product management Discover the ways different organizations describe and structure the product management role Explore the critical differences between product management "in theory" and "on-the-ground" Master the principles that guide successful product management Matt Lemay is cofounder of Constellate Data, a business intelligence research, consulting, and training company based in NYC. In his work as a technology communicator, Matt has developed and led product management and data strategy workshops for companies like GE, American Express, Pfizer, McCann, and Johnson & Johnson. Previously, Matt worked as a Senior Product Manager for the music startup Songza (acquired by Google) and as the Head of Consumer Product at Bitly